Effect of 2 mg versus 4 mg of intravenous zoledronic acid on bone mineral density at the lumbar Spine in Indian postmenopausal women with osteoporosis: A Double-blind parallel-arm randomized controlled trial - Harsh Durgia; Sadishkumar Kamalanathan; Govindarajalou Ramkumar; Sonali Sarkar; Sagili Vijaya Bhaskar Reddy; Jayaprakash Sahoo; Rajan Palui; Henith Raj (Wolters Kluwer Medknow Publications, 2021)
Objective: The primary purpose was to compare the effect of 2 mg and 4 mg of intravenous zoledronic acid (ZA) on change in the lumbar spine (LS) bone mineral density (BMD) at the end of 1 year in postmenopausal women with osteoporosis. The secondary objectives were changes in BMD at the total hip and femoral neck, change in bone turnover markers (BTMs), and the incidence of new fractures. Methods: This was a double-blind, parallel-arm, randomized control trial with an allocation ratio of 1:1 done in 70 postmenopausal women with osteoporosis. Findings: The mean (±standard deviation) percentage increase in LS BMD at the end of 1 year was 4.86% ± 3.05% and 5.35% ± 3.73% in the 2 mg and 4 mg group, respectively. The dose of 2 mg ZA proved to be inferior to 4 mg with a noninferiority margin of 0.5%. There was no difference in BMD change at hip and BTMs between the two groups at the end of 1 year. Only one patient in 4 mg group developed two new vertebral fractures during a 12-month follow-up. Acute-phase reactions were the most common (43%) side-effects noted without any difference between the two groups (P = 0.63). Conclusion: This study failed to show the noninferiority of 2 mg ZA compared to 4 mg ZA for change in LS BMD at the end of 1 year.